1993
DOI: 10.4319/lo.1993.38.6.1214
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen, carbon monoxide, and methane dynamics in Lake Constance

Abstract: The vertical distributions of dissolved H,, CO, and CH, and bacterial production (thymidine incorporation) were measured throughout 1987 in Lake Constance (Bodensee) and again in 1988 at a station in a small bight in the lake. Lake waters were supersaturated with respect to atmospheric H,, CO, and CH4, especially in the epilimnion; concentrations in the surface water showed a significant (P < 0.05) positive correlation with either autotrophic picoplankton, primary production, Chl a, pheophytin, or bacterial pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
61
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 24 publications
4
61
0
Order By: Relevance
“…Compared with emission rates reported in other literature (5.4 mg m-* d-l in summer and 12 1.6 during fall overturn at Lake 227, Rudd and Hamilton 1978;31.3 in summer and 38.4 during fall overturn at Lake Mendota, Fallon et al 1980), Lake Nojiri fluxes during overturn period appear to be low. The diffusive fluxes in this study were comparable to or slightly lower than those measured by Schmidt and Conrad (1993) for Lake Constance, by de Angelis and Lilley (1987) for Oregon rivers, and by de Angelis and Scranton (1993) for the Hudson River.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…Compared with emission rates reported in other literature (5.4 mg m-* d-l in summer and 12 1.6 during fall overturn at Lake 227, Rudd and Hamilton 1978;31.3 in summer and 38.4 during fall overturn at Lake Mendota, Fallon et al 1980), Lake Nojiri fluxes during overturn period appear to be low. The diffusive fluxes in this study were comparable to or slightly lower than those measured by Schmidt and Conrad (1993) for Lake Constance, by de Angelis and Lilley (1987) for Oregon rivers, and by de Angelis and Scranton (1993) for the Hudson River.…”
Section: Resultsmentioning
confidence: 62%
“…The distribution of CH, and CH, oxidation activity has been studied in several eutrophic (e.g. Jannasch 1975;Rudd et al 1974;Rudd and Hamilton 1978;Harrits and Hanson 1980;Iversen et al 1987) and oligotrophic lakes (Lidstrom and Somers 1984;Lilley et al 1988;Schmidt and Conrad 1993). Most reports have focused on dimictic lakes that have a seasonally formed anaerobic layer in the hypolimnion, and the studies have been done during the period of summer stratification.…”
mentioning
confidence: 99%
“…The relationship between CH 4 and phytoplankton observed here (Fig. 2) has been hypothesized before to explain both the presence of metabolically active methanogens, and the recurrent metalimnetic and near-surface CH 4 peaks in oxic lake 9,10,18,19 and marine [13][14][15][16][17] environments. We confirm this link experimentally, and further show that it generates a significant out flux of CH 4 from the mesocosms to the atmosphere (Fig.…”
Section: Discussionmentioning
confidence: 74%
“…This assumption certainly holds for small, shallow ecosystems where the surface layers are in relatively close contact with sediments. Yet CH 4 supersaturation is also prevalent in large, deep lakes 3,5,[7][8][9][10][11][12] and oceanic surface waters [13][14][15][16][17] , where deeper water columns result in significantly reduced surface water exchange with anoxic sediments. Studies of CH 4 dynamics in surface waters of oceans and large lakes have indeed concluded that pelagic CH 4 supersaturation cannot be sustained either by lateral inputs from the littoral or from benthic inputs alone 9,10,[13][14][15][17][18][19] .…”
mentioning
confidence: 99%
See 1 more Smart Citation